Perspektif Antropologi Hukum Dalam Penyelesaian Sengketa Masyarakat Melayu - Gatot Teguh Arifyanto; Andi Hakim Lubis (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This article aims to uncover alternative dispute resolutions from the perspective of the traditional and cultural institutions of the Malay community, Medang Deras District. To construct the research objectives, empirical legal research was conducted. This is because the primary research data are the words and actions of the research subjects. Based on the findings in the field, viewed from the perspective of legal anthropology, the alternative dispute resolution carried out by the Medang Deras Malay community is a combination of mediation and negotiation. This alternative is considered more effective and efficient than the litigation pathway. In this case, mediation and negotiation as traditional and cultural institutions of the Medang Deras Malay community are primarily determined by a neutral third party, termed obay.